Strategi Peningkatan Eksistensi Madrasah Ibtidaiyah (MI) di Kabupaten Rejang Lebong - Beni Azwar; Baryanto Baryanto; Rahmad Hidayat; Masudi Masudi (Journal Of Administration and Educational Management (ALIGNMENT), 2018)
The study aims at discussing the strategy to improve the existence of Madrasah Ibtidaiyah (MI) in Rejang Lebong regency. The research used sociological approach to comprehend the meaning of events and interaction of people in certain circumstances. The results were: Madrasah Ibtidaiyah (MI) was quite exist in assisting the education advance. It can be noticed by the work programs. The students were competitive and their achievements reached regional and national level. In conclusion, the strategy used to improve the existence of Madrasah Ibtidaiyah, such as using POAC strategy (planning organizing, actuating), as well as controling improved the existence of Madrasah Ibtidaiyah (MI) in Rejang Lebong regency. Keywords : Strategy, Existence, Madrasah Ibtidaiyah